The Role of Training Courses in Improving the Professional Performance of Principals in Private Schools in Bethlehem Governorate from their point of view - Hazboun, Grace Nasri (Journal of Educational and Psychological Sciences, 2024)
The study aimed to find out the role of training courses in improving the professional performance of male and female principals in private schools in Bethlehem Governorate from their point of view. The study adopted the descriptive survey approach for all principals of private schools in Bethlehem Governorate, numbering (35) principals. The number of questionnaire items was (30) items. In analyzing the data, the researcher relied on frequencies, percentages, and arithmetic averages for the questionnaire items. The study concluded that the effective role of training courses in all fields was emphasized. The study recommended that principals of private and non-private schools should pay great attention to training courses because of their benefits on improving professional performance, and focus on the needs of male and female managers for training when hiring them.